Socioeconomic Inequalities in Physical Activity in Brazil: A Pooled Cross-Sectional Analysis from 2013 to 2019 - De Moraes-Ferrari, G (BioMed Central Ltd, 2021)
Background: Information on socioeconomic inequalities in physical activity over time is sparse in low- to middle-income countries. In this study, we examined trends in physical activity educational inequalities in adults from Brazil between 2013 and 2019. Methods: We analyzed data from seven cross-sectional studies including 359,038 adults (≥ 18 years) from the VIGITEL study conducted annually from 2013 to 2019. Participants responded to a questionnaire about physical activity (total, leisure, and commuting). Educational inequalities by sex and skin color were assessed through absolute (slope index of inequality – SII) and relative measures of inequality (concentration index – CIX). Results: We found large absolute and relative inequalities for leisure-time physical activity, favoring those with higher educational attainment (SII2019 = 35.4; CIX2019 = 11.82). Active commuting was more prevalent in intermediate education groups, with a slight inequality toward the less educated group (SII2019 = -2.8; CIX2019 = -0.4). From 2013 to 2019, the absolute educational inequality in physical activity (total, leisure, and commuting) remained unchanged; however, the relative inequality gap narrowed for total physical activity (CIX: 8.4 in 2013 to 5.5 in 2019) and leisure-time physical activity (CIX: 18.3 in 2013 to 11.8 in 2019). Educational inequality increased in leisure-time physical activity among women and non-white individuals, while it reduced among men and white individuals; for active commuting, inequality decreased among women, and increased among men and white individuals. Conclusions: Inequality in total physical activity and leisure-time physical activity favors the most educated groups in Brazil. Over time, relative educational inequality decreased for total and leisure-time physical activity, while no progress was found for absolute inequality. © 2021, The Author(s).